2015
DOI: 10.2139/ssrn.2665151
|View full text |Cite
|
Sign up to set email alerts
|

Climate Shocks and (Very) Long-Run Productivity

Abstract: The present study examines the link between temperature and long-run productivity for a balanced panel of 21 countries, covering the period 1000-1800 CE. Collectively the countries examined accounted for about 2/3 of the global population by 1700. Each epoch in the analysis is a century long, which thus allows time for human adaptation after a temperature shock has occurred. Our principal …nding is that lower temperatures worked to reduce productivity growth during the period in focus, consistent with contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…There is also mounting evidence that weather and climate have important effects on societies. For example, a number of studies now show that cooling during the Little Ice Age resulted in worse health outcomes, social unrest, increased conflict, decreased productivity, and slower economic growth (e.g., Baten, 2002, Oster, 2004, Waldinger, 2015, Dalgaard et al, 2015, Iyigun et al, 2017. There is evidence that increased seasonal variability in certain locations resulted in the Neolithic transition, one of the most important social changes in human history (Matranga, 2016).…”
Section: Data: Sources and Their Construction A Motivating The Measumentioning
confidence: 99%
“…There is also mounting evidence that weather and climate have important effects on societies. For example, a number of studies now show that cooling during the Little Ice Age resulted in worse health outcomes, social unrest, increased conflict, decreased productivity, and slower economic growth (e.g., Baten, 2002, Oster, 2004, Waldinger, 2015, Dalgaard et al, 2015, Iyigun et al, 2017. There is evidence that increased seasonal variability in certain locations resulted in the Neolithic transition, one of the most important social changes in human history (Matranga, 2016).…”
Section: Data: Sources and Their Construction A Motivating The Measumentioning
confidence: 99%
“…This climate event probably affected farming practices and crops, causing economic crises (e.g. Le Roy Ladurie, 2006;Dalgaard et al, 2015). The combined effect of climate and land use on vegetation demonstrates the existence of early feedback loops between climate, land use and vegetation and this becomes stronger over the last millennia towards the present.…”
Section: Regionsmentioning
confidence: 99%
“…There is also evidence that weather and climate have important effects on societies. It has been shown that cooling during the Little Ice Age resulted in worse health outcomes, social unrest, increased conflict, decreased productivity, and slower economic growth (Baten, 2002, Oster, 2004, Waldinger, 2015, Dalgaard, Hansen and Kaarsen, 2015, Iyigun, Nunn and Qian, 2017. Matranga (2016) argues that increased seasonal variability in certain locations resulted in the Neolithic transition, one of the most important social changes in human history.…”
Section: A Motivating the Measure Of Environmental Instabilitymentioning
confidence: 99%